Numerical and experimental investigations on cavity roughness effects in micro injection molding - Zhang, Hong Lin (2010)
Injection molding is one of the most common processes for cost-effective mass production of plastic micro parts. In micro injection molding, cavity surface roughness, which is insignificant in conventional (or macro) molding, may play an important role. Although the roughness effects in micro injection molding were mentioned in some research, they were not investigated systematically and understood clearly. In this thesis, the roughness effects on cavity filling in micro injection molding were for the first time mathematically modeled and systematically investigated through experiment and numerical simulation.